Travel medicine : knowledge, attitude, practice and immunisation - Roukens, Anna Helena Elvire, 1979- (IOS Press, 2010)
Along with the dramatic 6% per annum increase in global travel in recent years, has come an increased potential risk for the spread of disease. The wide variety of people traveling by many different means requires a diverse approach to protection against travel-related illness and disease risk. This book addresses the subject of travel medicine and improving protection, with regard particularly to the areas of epidemiology and prevention, morbidity and mortality, adherence to precautions, immunological responsivity and the availability of preventive measures. Following a general introduction providing background information and a historical perspective, the topics examined in detail include: how travelers' knowledge and attitudes can be influenced with training, the implications of travel for a number of special groups such as kidney transplant recipients, diabetics and the healthy elderly, and immunity and vaccine issues for diseases such as Hepatitis B, yellow fever and rabies. Of interest to all those involved in any aspect of travel medicine, the book concludes with a general discussion, which also contemplates future research perspectives for the field. - Publisher.